2012
DOI: 10.1155/2012/871495
|View full text |Cite|
|
Sign up to set email alerts
|

Management of Diabetes and Its Complications with Banaba (Lagerstroemia speciosaL.) and Corosolic Acid

Abstract: Banaba (Lagerstroemia speciosa L.) extracts have been used for many years in folk medicine to treat diabetes, with the first published research study being reported in 1940. This paper summarizes the current literature regarding Banaba and its constituents. The hypoglycemic effects of Banaba have been attributed to both corosolic acid as well as ellagitannins. Studies have been conducted in various animal models, human subjects, and in vitro systems using water soluble Banaba leaf extracts, corosolic acid, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
29
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 42 publications
0
29
0
2
Order By: Relevance
“…Traditionally, tea made from banaba leaves has been used to treat diabetes mellitus in Southeast Asia [13]. Recently, it has been reported that L. speciosa leaf extract has extensive antidiabetic, antiobesity [14], anti-inflammatory, antioxidant, antiviral, antibacterial [12], anti-hypertensive [15], antifibrotic [16] and analgesic [17] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, tea made from banaba leaves has been used to treat diabetes mellitus in Southeast Asia [13]. Recently, it has been reported that L. speciosa leaf extract has extensive antidiabetic, antiobesity [14], anti-inflammatory, antioxidant, antiviral, antibacterial [12], anti-hypertensive [15], antifibrotic [16] and analgesic [17] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological activities of CA include antidiabetic [4,5], antibacterial [6], anti-inflammatory [7][8][9], anti-obesity [9][10][11], anti-atherosclerosis [7,12], cholesterol-reducing [13], osteoblast differentiation [14], antioxidant [15,16], and hepatoprotective [16,17] properties. Among these biological activities, the antidiabetic properties of CA are well documented [18][19][20][21][22][23][24][25] with several clinical trials conducted [26,27] and patents applied [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Corosolic acid is also able to inhibit the differentiation of adipocytes, making it useful in the treatment of overweight and obesity. It seems also that banaba can lower blood glucose levels, also acts on fat in the liver by reducing the accumulation of triglycerides, which would also have a positive effect on cholesterol (16).…”
Section: Introductionmentioning
confidence: 99%